The Genetic Basis of Turner Syndrome Aortopathy - Corbitt, Holly (Am J Med Genet C Semin Med Genet, 2019)
Our goal is to identify the genetic underpinnings of bicuspid aortic valve and aortopathy in Turner syndrome. We performed whole exome sequencing on 188 Turner syndrome study subjects from the GenTAC registry. A gene-based burden test, SKAT-O, was used to evaluate the data using bicuspid aortic valve (BAV) and aortic dimension z-scores as covariates. This revealed that TIMP3 was associated with BAV and increased aortic dimensions at exome-wide significance. It had been previously shown that genes on chromosome Xp contribute to aortopathy when hemizygous. Our analysis of Xp genes revealed that hemizygosity for TIMP1, a functionally redundant paralogue of TIMP3, increased the odds of having BAV aortopathy compared to individuals with more than one TIMP1 copy. The combinatorial effect of a single copy of TIMP1 and TIMP3 risk alleles synergistically increased the risk for BAV aortopathy to nearly 13-fold. TIMP1 and TIMP3 are tissue inhibitors of matrix metalloproteinases (TIMPs) which are involved in development of the aortic valve and protection from thoracic aneurysms. We propose that the combination of TIMP1 haploinsufficiency and deleterious variants in TIMP3 significantly increases the risk of BAV aortopathy in Turner syndrome, and suggest that TIMP1 hemizygosity may play a role in euploid male aortic disease.